A novel cobalt oxide nanoparticle conjugated with ellagic acid arrests the cell cycle in human liver cancer cell line - Ayda Mahmoudi; Vajiheh Zarrin Pour; Ali Salehzadeh (Scientific Reports)
Abstract The current chemotherapy treatments for liver cancer have shown limited effectiveness. Therefore, there is an urgent need to develop new drugs to combat this disease more effectively. This study reports synthesis of cobalt oxide nanoparticles coated with glucose, and conjugated with Ellagic acid. Physicochemical characterization of Co3O4@Glu-Ellagic acid nanoparticles was done using FT-IR, XRD, SEM, TEM, TGA, EDS-mapping, DLS, and zeta potential analyses, and the investigation of their anticancer potential on liver cancer cell lines involved the use of MTT, flow cytometry, and cell cycle analysis. The synthesized nanoparticles were somewhat spherical, arranged in a relatively cluster-shaped form, and were 33–46 nm in diameter. The zeta potential and particle hydrodynamic size were − 5.43 and 169 nm, respectively and had no elemental impurity. Also, the synthesized particles had proper thermal stability at temperatures below 100 °C. Treating cancer cells with the nanoparticles considerably increased ROS levels by 2.6 folds. Compared to normal human cells, Co3O4@Glu-Ellagic acid nanoparticles showed significantly higher toxicity for liver cancer and the 50% inhibitory concentration was 94 and 187 µg/mL for the cancer and normal cells, respectively. Co3O4@Glu-Ellagic acid increased cell apoptosis, from 0.87 to 9.24%, and the cells were mainly arrested at the G0/G1 and G2/M phases. Overall, the present work indicated that Co3O4@Glu-Ellagic acid has antiproliferative effects on liver cancer cells through an increased oxidative stress level, inhibition of cell cycle, and apoptosis induction.